PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT IN THE ADAPTATION OF UNIVERSITY STUDENTS - Sharakhmatova A. K. (Modern American Journals, 2025)
Modern trends in education generate unique challenges for students during their adaptation to higher education institutions. To address these challenges, psychological and pedagogical support emerges as a comprehensive and systematic activity aimed at creating favorable conditions for adaptation. This article examines the theoretical foundations, forms, and principles of psychological and pedagogical support in the adaptation of first-year university students. Based on a review of scholarly perspectives and pedagogical practices, the study defines the essence of support as a technology that facilitates personal development, education, upbringing, and socialization of students. The paper also outlines the stages of adaptation support and emphasizes the role of tutors, teachers, and parents in this process.
Keywords: Adaptation, higher education, psychological and pedagogical support, tutoring, student development.